Nanoparticles for enhancing the bioavailability of coenzyme Q10 and preparation method and use thereof

By using metal organic frame nanoparticles to carry Coenzyme Q10, the problem of low bioavailability is solved, and higher bioavailability and antioxidant effects are achieved. It is suitable for the application of drugs, health products or cosmetics.

CN117137888BActive Publication Date: 2025-04-15WANG SHUHE BIOMEDICINE (WUHAN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310887741.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-04-15
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

Coenzyme Q10 is low in bioavailability due to its lipophilicity and low water solubility, which limits its application.

Method used

Metal organic frame (MOF) nanoparticles are used as carriers, and MIL-101(Fe)-NH2 is used as the core and oxidized hyaluronic acid (OHA) is used as the shell. The physical method is used to carry Coenzyme Q10 to improve its bioavailability.

Benefits of technology

提高了辅酶Q10的生物利用度,延长了其释放时间,增强了其抗氧化效果,并且纳米粒子的稳定性和可控释特性使其在药品、保健品或化妆品中具有应用潜力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117137888B_ABST
    Figure CN117137888B_ABST
Patent Text Reader

Abstract

The present invention discloses a nanoparticle for enhancing the bioavailability of coenzyme Q10 and a preparation method and use thereof, and relates to the field of pharmaceutical preparations. The nanoparticle comprises the following steps: (1) MIL-101(Fe)-NH 2 Preparation: Dissolve terephthalic acid and ferric chloride hexahydrate in DMF, stir and heat to react to obtain MIL‑101(Fe)‑NH 2 ; (2) Preparation of oxidized hyaluronic acid OHA; (3) Preparation of Q10 / MIL-101(Fe)-OHA: MIL-101(Fe)-NH 2 Dispersed in deionized water, MIL‑101(Fe)‑NH 2 The dispersion is prepared by sequentially adding a coenzyme Q10 solution dissolved in water and OHA dissolved in PBS buffer to the dispersion, stirring the mixture in the dark, washing by centrifugation, and drying overnight to obtain the coenzyme Q10-loaded nanoparticles Q10 / MIL-101(Fe)-OHA. The nanoparticles prepared by the present invention have better stability. 2 The nanoparticles are based on the core and oxidized hyaluronic acid (OHA) as the shell. Coenzyme Q10 is encapsulated by physical methods and has controlled release characteristics. At the same time, the nanoparticles can carry a large amount of cargo, which is conducive to carrying coenzyme Q10 into cells, and can effectively improve the bioavailability of coenzyme Q10 and enhance the antioxidant effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of pharmaceutical preparations, and in particular to a nanoparticle capable of enhancing the bioavailability of coenzyme Q10, and a preparation method and application thereof. Background Art

[0002] Coenzyme Q10 10 ,CoQ 10 ), also known as pan-wake and vitamin Q, has a structure similar to common vitamin K. It is a fat-soluble compound and a natural antioxidant. It is widely present in human tissues, but its specific content will continue to decrease with age. 75% of the coenzyme Q10 contained in the human body comes from the body's own synthesis, and 25% is obtained through daily diet. Coenzyme Q10 can help the human body convert the food it eats into energy for the body to use, and plays an important role in the process of human energy production. Therefore, coenzyme Q10 is mainly concentrated in energy-consuming organs such as the heart, liver, and kidneys. Coenzyme Q10 mainly exists in two forms: oxidized and reduced. Most of it exists in the reduced form in the human body. Reduced coenzyme Q10 is easily oxidized and can play an antioxidant role similar to vitamin E. Both have a powerful free radical scavenging effect, reduce the damage of free radicals to the body, and maintain the health of the body.

[0003] However, the application of coenzyme Q10 is greatly limited due to its strong lipophilicity and extremely low water solubility. At the same time, the existing coenzyme Q10 on the market also has the problem of low bioavailability.

[0004] Therefore, providing a nanoparticle that can load coenzyme Q10 to improve its bioavailability and improve its water solubility is an urgent problem to be solved by the present invention. Summary of the invention

[0005] The present invention provides a nanoparticle for enhancing the bioavailability of coenzyme Q10, and a preparation method and use thereof, aiming to solve the problems existing in the above-mentioned background technology.

[0006] In order to achieve the above technical objectives, the present invention mainly adopts the following technical solutions:

[0007] In a first aspect, the present invention discloses a method for preparing nanoparticles for enhancing the bioavailability of coenzyme Q10, comprising the following steps:

[0008] (1) Preparation of MIL-101(Fe)-NH2: dissolving terephthalic acid and ferric chloride hexahydrate in DMF, stirring and heating to react, cooling the reaction solution to room temperature and centrifuging to obtain a brick-red precipitate, washing and drying the precipitate to obtain MIL-101(Fe)-NH2;

[0009] (2) Preparation of oxidized hyaluronic acid OHA: add a strong oxidant to the hyaluronic acid HA solution, stir and react for a period of time at room temperature in the dark, then add ethylene glycol, continue stirring, dialyze with pure water, and freeze-dry to obtain oxidized hyaluronic acid OHA containing two aldehyde groups;

[0010] (3) Preparation of Q10 / MIL-101(Fe)-OHA: The MIL-101(Fe)-NH2 prepared in step (1) was dispersed in deionized water to obtain a MIL-101(Fe)-NH2 dispersion, and then a coenzyme Q10 solution dissolved in water and OHA dissolved in PBS buffer were sequentially added to the MIL-101(Fe)-NH2 dispersion. The reaction was stirred in the dark, and the reaction solution was centrifuged for washing and dried overnight to obtain the product, coenzyme Q10-loaded nanoparticles Q10 / MIL-101(Fe)-OHA.

[0011] In a preferred embodiment of the present invention, in step (1), the mass ratio of terephthalic acid to ferric chloride hexahydrate is 1:3-3.5, preferably, the mass ratio of terephthalic acid to ferric chloride hexahydrate is 1:3.29.

[0012] In a preferred embodiment of the present invention, in step (1), the reaction temperature is 100-120°C, and the reaction time is 18-24h. Preferably, the reaction temperature is 110°C, and the reaction time is 20h.

[0013] In a preferred embodiment of the present invention, in step (2), the concentration of the hyaluronic acid HA solution is 10 mg / mL, and the strong oxidant is sodium periodate.

[0014] Furthermore, in step (2), the mass ratio of the hyaluronic acid HA to the sodium periodate is 1-1.5:1, and preferably, the mass ratio of the hyaluronic acid HA to the sodium periodate is 1.25:1.

[0015] Furthermore, in step (2), the volume ratio of the added amount of ethylene glycol to the hyaluronic acid HA solution is 1:8.

[0016] In a preferred embodiment of the present invention, in step (3), the mass ratio of MIL-101(Fe)-NH2 to coenzyme Q10 and oxidized hyaluronic acid OHA is 10:1:10.

[0017] In a preferred embodiment of the present invention, in step (3), the PBS buffer concentration is 0.2 M, pH 7.4.

[0018] In a second aspect, the present invention discloses a nanoparticle for enhancing the bioavailability of coenzyme Q10 prepared by the preparation method described in the first aspect, wherein the nanoparticle has a spherical morphology and hyaluronic acid is coated on the surface of the nanoparticle.

[0019] Hyaluronic acid (HA), as a natural polymer, is biodegradable, biocompatible, low-toxic and non-immunogenic among various polymers, and has antioxidant and anti-aging effects.

[0020] In a third aspect, the present invention discloses a use of the nanoparticles for enhancing the bioavailability of coenzyme Q10 as described in the second aspect in the preparation of medicines, health products or cosmetics with antioxidant and anti-aging effects.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] Metal-organic framework (MOFs) is a new type of porous crystalline material assembled by coordination chemistry with inorganic metal ions as the center and organic linkers as ligands. The surface of MOF has rich functional groups and a large internal cavity. This large specific surface area enables it to be used as a carrier. At the same time, the shape and size can be adjusted, and coenzyme Q10 can be loaded to improve its bioavailability. The nanoparticles prepared by the present invention use metal organic framework (MOF) as a nanoparticle carrier with better stability, MIL-101 (Fe) -NH2 as the core and oxidized hyaluronic acid (OHA) as the shell, and coenzyme Q10 is encapsulated by physical methods, and has controlled release characteristics. At the same time, the nanoparticles are loaded with a large amount of cargo, which is conducive to carrying coenzyme Q10 into cells, and can effectively improve the bioavailability of coenzyme Q10 and enhance the antioxidant effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the Fourier infrared characterization spectrum of MIL-101(Fe)-NH2;

[0024] Figure 2 It is the Fourier infrared characterization spectrum of hyaluronic acid HA and oxidized hyaluronic acid OHA;

[0025] Figure 3 This is the dynamic light scattering test diagram of nanoparticles Q10 / MIL-101(Fe)-OHA;

[0026] Figure 4 This is a linear regression equation diagram of the drug loading of the drug delivery nanoparticles Q10 / MIL-101(Fe)-OHA of the present invention;

[0027] Figure 5This is a comparative chart of the drug release rate of unmodified Q10 and nanoparticle Q10 / MIL-101(Fe)-OHA;

[0028] Figure 6 This is the result of the pH stability study of nanoparticles Q10 / MIL-101(Fe)-OHA;

[0029] Figure 7 is the TEM image of nanoparticles Q10 / MIL-101(Fe)-OHA;

[0030] Figure 8 This is a comparison chart of the scavenging ability of coenzyme Q10, HA, a mixture of Q10 and HA, and Q10 / MIL-101(Fe)-OHA on DPPH. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The reagents not described separately in detail in the present invention are all conventional reagents and can be obtained from commercial channels; the methods not described in detail are all conventional experimental methods and can be obtained from the prior art.

[0032] Example 1

[0033] Preparation of Coenzyme Q10-Carrying Nanoparticles Q10 / MIL-101(Fe)-OHA

[0034] (1) Preparation of MIL-101(Fe)-NH2: 206 mg of terephthalic acid and 675 mg of ferric chloride hexahydrate were dissolved in 30 mL of DMF, stirred at room temperature for 30 minutes to mix the two substances evenly, and then reacted in an oil bath at 110°C for 20 hours. After the reaction, the reaction solution was cooled to room temperature and centrifuged to obtain a brick-red precipitate, which was then cross-washed with anhydrous ethanol and DMF for more than five times and vacuum dried to obtain a brick-red powdery solid product named MIL-101(Fe)-NH2.

[0035] The Fourier transform infrared spectrum of MIL-101(Fe)-NH2 was characterized, such as Figure 1 As shown in Figure 1, the characteristic infrared spectrum of MIL-101(Fe)-NH2 mainly reflects benzene carboxylate. -1 The band at 1385.37 cm is attributed to the C=O bond in the carboxylate. -1 It is attributed to the CC vibration absorption peak of aromatic carbon. 1265cm -1The spectral band at is the characteristic absorption peak of the amine group, corresponding to the stretching vibration of the aromatic carbon CN bond, confirming the successful synthesis of MIL-101(Fe)-NH2.

[0036] (2) Preparation of oxidized hyaluronic acid (OHA): Hyaluronic acid (HA) was prepared into a 10 mg / mL solution. 320 mg of sodium periodate was dissolved in 10 mL of deionized water and then added dropwise to 40 mL of HA solution. The mixture was stirred in the dark at room temperature for 24 h. Then 5 mL of ethylene glycol was added and stirred for 30 min. The mixture was dialyzed with pure water for 48 h and freeze-dried to obtain oxidized hyaluronic acid (OHA) containing two aldehyde groups.

[0037] The oxidized hyaluronic acid (OHA) was characterized by Fourier transform infrared spectroscopy. Figure 2 As shown in the figure, the FT-IR spectra of hyaluronic acid HA and oxidized hyaluronic acid OHA are compared. -1 The increased absorption peak at

[0038] (3) Preparation of coenzyme Q10-loaded nanoparticles Q10 / MIL-101(Fe)-OHA: 50 mg of MIL-101(Fe)-NH2 was dispersed in deionized water, 5 mg of coenzyme Q10 was dissolved in 3 mL of water and then added to the MIL-101(Fe)-NH2 dispersion and mixed evenly, 50 mg of OHA was dissolved in 10 mL of PBS (0.2 M) buffer (pH 7.4), added to the above suspension, stirred in the dark at 25°C for 24 h, centrifuged and washed, the supernatant was retained, the drug loading was tested later, and then dried overnight to obtain the product Q10 / MIL-101(Fe)-OHA.

[0039] The average particle size of the prepared Q10 / MIL-101(Fe)-OHA was determined by dynamic light scattering and Malvern particle size analyzer: a 0.5 mg / mL nanoparticle Q10 / MIL-101(Fe)-OHA solution was prepared, ultrasonicated for 10 minutes, and then placed in a dynamic light scattering instrument for testing. Figure 3 As shown, the average hydrated particle size of the drug-loaded nanoparticles Q10 / MIL-101(Fe)-OHA is 180 nm.

[0040] The surface morphology of the nanoparticles was observed using a transmission electron microscope. A 1 mg / mL nanoparticle Q10 / MIL-101(Fe)-OHA dispersion was prepared and added to a 200-mesh carbon film copper grid. After about 1 minute, the excess solution on the copper grid was absorbed with filter paper. After the copper grid was dried naturally, the morphology and size of the nanocarrier were observed using a transmission electron microscope (TEM). The results are shown in Figure 2. Figure 7 shown.

[0041] Depend on Figure 7 It can be observed that the particle size (dry sample) of the modified nanoparticles Q10 / MIL-101(Fe)-OHA is about 110 nm, showing a spherical morphology, and the fuzzy layer on the surface indicates that hyaluronic acid is successfully wrapped on its surface.

[0042] Test Example 1

[0043] Determination of drug loading of the drug delivery nanometer system of the present invention

[0044] Determination of the standard curve of Q10: Prepare 0, 3, 6, 12, 24, 36, 48 μg / mL Q10 ethanol solutions, shake well, and number them 0-6. Take 3 mL of ethanol solution as blank, use UV / visible light / infrared spectrophotometer, continuously measure the absorbance A of solution No. 0-6 at a wavelength of 275 nm, after obtaining A, perform linear regression analysis through concentration C, and obtain the standard curve of Q10. Use UV absorption detector to detect the absorption value of the supernatant retained in step (3) of Example 1 at a wavelength of 275 nm, which is the amount of coenzyme Q10 not loaded. Use Vis-UV method to measure and calculate the coenzyme Q10 content in the nanocarrier: Encapsulation efficiency EE% = C 包埋Q10 / C 总Q10 ×100%.

[0045] like Figure 4 As shown, the standard curve equation is Y = 0.0145X-0.0229, and the linear regression coefficient R 2 =0.9995, indicating that the standard curve has good correlation and high accuracy in the effective concentration range of 2μg / mL to 48μg / mL. The encapsulation efficiency is 90.02%.

[0046] Test Example 2

[0047] Study on the drug release rate of Q10 / MIL-101(Fe)-OHA

[0048] 2mL of the prepared Q10 / MIL-101(Fe)-OHA solution was placed in a dialysis bag (Mw=14000kDa). The release medium was prepared from Tween 80, ethanol and phosphate buffer solution (pH=5.8) (volume ratio of 5:20:75), and the dialysis bag was placed in a 250mL beaker filled with 200ml of the release medium. The release medium was maintained at 32°C and stirred continuously at 200rpm. At 0, 1, 2, 4, 6, 8, 10, 12, and 24 hours, 3mL of the release medium was taken and the same volume of fresh release medium was immediately added. The effect of pH on the coenzyme Q10-loaded nanosystem was investigated by measuring the cumulative release of coenzyme Q10 over a certain period of time and plotting it as a function of time.

[0049] like Figure 5As shown, the unmodified Coenzyme Q10 reached the maximum release rate at 24h, while the release rate of Coenzyme Q10 in Q10 / MIL-101(Fe)-OHA modified with nanoparticles was 32.12% at 24h, indicating that the modification of nanoparticles can prolong the release time of Coenzyme Q10.

[0050] Test Example 3

[0051] Study on pH Stability of Q10 / MIL-101(Fe)-OHA

[0052] Cur is very sensitive to environmental pH. Studies have shown that more than 90% of Cur decomposes rapidly under neutral or alkaline conditions. In order to evaluate the pH sensitivity of Q10 / MIL-101(Fe)-OHA, it was placed in an alkaline environment with different pH values ​​(pH = 7.0, 8.0, 9.0, 10.0, 11.0 and 12.0). Q10 / MIL-101(Fe)-OHA was first centrifuged and resuspended in PBS. The pH value of the solution was adjusted to a preset value using a 2M NaOH solution. Then, the Q10 / MIL-101(Fe)-OHA sample was mixed with PBS in a volume ratio of 1:9. The resulting mixture was allowed to stand at room temperature for 1 hour, and then the amount of Q10 retained in the nanoparticles was measured by absorbance. Retention% = C 处理后样品Q10 / C 新制样品Q10 ×100%.

[0053] like Figure 6 As shown in the figure, when the pH value increases from 7 to 9, Q10 / MIL-101(Fe)-OHA maintains a Q10 retention rate of more than 98%. The pH stability of coenzyme Q10 in Q10 / MIL-101(Fe)-OHA is higher than that of free coenzyme Q10. At pH 9.0, its Q10 retention rate is 98.8%. The data when the pH value increases from 7 to 9 show that the metal organic framework MIL-101(Fe)- and hyaluronic acid can protect Q10 from degradation and help prevent leakage from Q10 nanoparticles. However, when the pH value increases from 9 to 12, the pH stability of coenzyme Q10 in Q10 / MIL-101(Fe)-OHA is significantly reduced. This is because MIL-101(Fe)- and hyaluronic acid are unstable under strong alkaline conditions, resulting in leakage of encapsulated coenzyme Q10.

[0054] Test Example 4

[0055] Study on the Antioxidant Properties of Q10 / MIL-101(Fe)-OHA

[0056] The in vitro antioxidant activity of the nanoparticles was evaluated by DPPH free radical scavenging test. 14 mg DPPH was dissolved in 50 mL ethanol and dispersed evenly in an ultrasonic water bath. After that, the reference substance coenzyme Q10 was dissolved in ethanol and its concentration was adjusted to the same concentration of coenzyme Q10 in the Q10 / MIL-101(Fe)-OHA solution (0.01 mg / mL) by UV spectrophotometer. Because HA itself has antioxidant effects, 0.1 mg / mL HA was selected for the experiment.

[0057] First, nanoparticle Q10 / MIL-101(Fe)-OHA, sample coenzyme Q10, sample HA, and a mixture of sample coenzyme Q10 and HA were configured into 4 groups of samples, and then the 4 groups of samples were fully mixed with DPPH solution at a ratio of 1:1 and incubated in the dark at 37°C for 30 minutes. Secondly, deionized water was used instead of nanoparticle Q10 / MIL-101(Fe)-OHA to prepare a control group, and anhydrous ethanol was used instead of DPPH solution as a blank group. Immediately after 30 minutes, the absorbance of the mixture was detected at 515nm. The lower the absorbance of the mixture, the higher the free radical scavenging activity, and vice versa. The scavenging ability of DPPH was calculated according to the following equation:

[0058] DPPH clearance rate (%) = [1 – (A 样本 –A 空白 ) / A 对照 ]×100%

[0059] The results are as follows Figure 8 As shown, the scavenging ability of coenzyme Q10 before modification and HA in the control group on DPPH was only 6.7±0.5% and 9.8±1.3%, respectively. After mixing coenzyme Q10 and HA, the scavenging ability of DPPH was 16.5±0.8%, indicating that the mixture of the two can synergistically enhance the antioxidant effect. The scavenging ability of modified Q10 / MIL-101(Fe)-OHA on DPPH was 25.5±1.6%, which was higher than that of the mixture group, indicating that the antioxidant effect of coenzyme Q10 was improved after modification.

[0060] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing nanoparticles for enhancing the bioavailability of coenzyme Q10, characterized in that: The steps include: (1) Preparation of MIL-101(Fe)-NH2: 2-aminoterephthalic acid and ferric chloride hexahydrate were dissolved in DMF, stirred and heated for reaction, and after the reaction was completed, the reaction solution was cooled to room temperature and centrifuged to obtain a brick red precipitate, and the precipitate was washed and dried to obtain MIL-101(Fe)-NH2; (2) Preparation of oxidized hyaluronic acid OHA: add a strong oxidant to the hyaluronic acid HA solution, stir and react for a period of time at room temperature in the dark, then add ethylene glycol, continue stirring, dialyze with pure water, and freeze-dry to obtain oxidized hyaluronic acid OHA containing two aldehyde groups; (3) Preparation of Q10 / MIL-101(Fe)-OHA: The MIL-101(Fe)-NH2 prepared in step (1) was dispersed in deionized water to obtain a MIL-101(Fe)-NH2 dispersion, and then a coenzyme Q10 solution dissolved in water and OHA dissolved in PBS buffer were sequentially added to the MIL-101(Fe)-NH2 dispersion. The reaction was stirred in the dark, and the reaction solution was centrifuged and washed, and dried overnight to obtain the product coenzyme Q10-loaded nanoparticles Q10 / MIL-101(Fe)-OHA. Wherein, the mass ratio of MIL-101(Fe)-NH2 to coenzyme Q10 and oxidized hyaluronic acid OHA is 10:1:10; When the pH value increased from 7 to 9, Q10 / MIL-101(Fe)-OHA maintained the Q10 retention rate above 98%.

2. The method for preparing nanoparticles for enhancing the bioavailability of coenzyme Q10 according to claim 1, characterized in that: In step (1), the mass ratio of 2-aminoterephthalic acid to ferric chloride hexahydrate is 1:3-3.

5.

3. The method for preparing nanoparticles for enhancing the bioavailability of coenzyme Q10 according to claim 1, characterized in that: In step (1), the reaction temperature is 100-120° C. and the reaction time is 18-24 h.

4. The method for preparing nanoparticles for enhancing the bioavailability of coenzyme Q10 according to claim 1, characterized in that: In step (2), the concentration of the hyaluronic acid HA solution is 10 mg / mL, and the strong oxidant is sodium periodate.

5. The method for preparing nanoparticles for enhancing the bioavailability of coenzyme Q10 according to claim 4, characterized in that: In step (2), the mass ratio of the hyaluronic acid HA to the sodium periodate is 1-1.5:

1.

6. The method for preparing nanoparticles for enhancing the bioavailability of coenzyme Q10 according to claim 5, characterized in that: In step (2), the volume ratio of the added amount of ethylene glycol to the hyaluronic acid HA solution is 1:

8.

7. The method for preparing nanoparticles for enhancing the bioavailability of coenzyme Q10 according to claim 1, characterized in that: In step (3), the PBS buffer concentration is 0.2 M, pH 7.

4.

8. The nanoparticles for enhancing the bioavailability of coenzyme Q10 prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The nanoparticles are in a spherical shape, and hyaluronic acid is coated on the surface of the nanoparticles.

9. Use of the nanoparticles for enhancing the bioavailability of coenzyme Q10 as claimed in claim 8 in the preparation of medicines, health products or cosmetics with antioxidant and anti-aging effects.